(untitled) (Baghdad Science Journal, 2010)
Ciphers can be either symmetric-key or public-key. Symmetric-key ciphers are the most famous and important elements in many cryptographic systems. Individually, they provide confidentiality and privacy. The Aim of this paper is to Apply symmetric block ciphers algorithm which is called Tiny Encryption algorithm (TEA). There are many types of block cipher use different techniques and functions using basic arithmetic operations such as XOR, addition, subtraction, multiplication, bitwise shift, and division. TEA cipher uses XOR, addition and bitwise shift. The paper presents how a block cipher could be constructed in general, it includes an observation of the history, inventors, and algorithms of the TEA block ciphers. It also discuss the manner did the programming took in terms of modularity, simplicity, resource reservation, in the previous algorithm the user cannot enter the plain text as a characters, it must enter the ASCII cod of the characters we write a lot e of functions to solve this problem also we enable the user to save his message in text file to make him use it to receive a message from email ,Also the time of encryption and decryption are calculated to measure the performance of the algorithm., The implementation of TEA is made using C/C++ Borland compiler version( 4.5).